Nucleolar activity during larval development of Myrmeleon uniformis Navas, 1920 (Neuroptera, Myrmeleontidae) - Pacheco, C. A.; Alevi, K. C. C. [UNESP]; Silva, T. L. [UNESP]; Azeredo-Oliveira, M. T. V. [UNESP]; Ceron, C. R. [UNESP]; Kobayashi, M. K. H. [UNESP] (Funpec-editora, 2014)
It has been reported in the literature that the Malpighian tubules of Neuroptera in the third instar undergo drastic histological changes, when they stop functioning in osmoregulation and start to secrete silk fibers for a cocoon. Therefore, to increase our knowledge about these cellular alterations that occur in the larvae of Neuroptera, we analyzed the cells that constitute the Malpighian tubules of each larval instar of the species Myrmeleon uniformis, with emphasis on nucleolar activity. Malpighian tubules, after being removed, were fixed on a slide using liquid nitrogen and stained by silver impregnation. In addition, total protein of the tubules was quantified. By analyzing the cells in the first instar larval stage, we observed only two silver-stained nucleolar regions. In cells of second instar larvae, there was an increase in the number of stained regions, and in the third instar, the number of nucleolar regions was very large. Agarose gel electrophoresis indicated that third instar larvae had high synthetic activity, where the total amount of proteins was larger in third instar stage than in the other larval stages. Furthermore, the most abundant proteins displayed molecular weights of about 32-43 kDa and were probably precursors of silk fibers. Thus, the results obtained showed that nucleolar alterations occur in the cells of the Malpighian tubules of larval instars of M. uniformis and this is directly related to the production of silk fibers used by the pupa to ensure the completion of metamorphosis.
Keywords: Cytochemical; Myrmeleon uniformis; Silver impregnation; Nucleolus